2018
DOI: 10.1080/13596748.2018.1420684
|View full text |Cite
|
Sign up to set email alerts
|

‘Mapping backward’ and ‘looking forward’ by the ‘invisible educators’ – reimagining research seeking ‘common features of effective teacher preparation’

Abstract: Mapping backward' and 'looking forward' by the 'invisible educators'-reimagining research seeking 'common features of effective teacher preparation'', Research in Post-Compulsory Education, 23 (1). pp. 23-34.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Skimming recent studies, we found the term ëgood teacherí (Baier et al, 2019;Duarte, 2013;Souto-Manning, 2019;Stronge et al, 2011) or even ëgood enough teacherí (Gillespie & Thompson, 2021;Thompson & Jones, 2021). However, the term ëeffective teacher or teachingí has also been used instead for some time (Crawley, 2018;Goodley, 2018). Some authors also use terms such as quality teachers (Buchanan, 2017) or professional teachers (Gerrard & Farrell, 2014).…”
Section: Defining a Good Teacher For Today And Tomorrowmentioning
confidence: 86%
“…Skimming recent studies, we found the term ëgood teacherí (Baier et al, 2019;Duarte, 2013;Souto-Manning, 2019;Stronge et al, 2011) or even ëgood enough teacherí (Gillespie & Thompson, 2021;Thompson & Jones, 2021). However, the term ëeffective teacher or teachingí has also been used instead for some time (Crawley, 2018;Goodley, 2018). Some authors also use terms such as quality teachers (Buchanan, 2017) or professional teachers (Gerrard & Farrell, 2014).…”
Section: Defining a Good Teacher For Today And Tomorrowmentioning
confidence: 86%
“…Instead, what now exists is a suite of qualifications which cover the development of the mechanics of teaching in general terms, understanding of the TVET sector and importantly research approaches to improving practice. However, TVET and the training of TVET teachers is an unresearched area of practice (Crawley, 2018;Springbett, 2018).…”
Section: Vocational Knowledge and Pedagogymentioning
confidence: 99%
“…Publicly-funded ITE programmes are inspected by the Office for Standards in Education, Children's Services and Skills (Ofsted), whose inspection frameworks are as influential in curriculum termsif not more sothan the qualifications framework. The FE and Skills sector is under-researched, and in particular little is known about teacher educators or their professional activities (see Noel, 2006;Author2, 2007;Crawley, 2018;Springbett, 2018). This paper examines how teacher educators for the FE and Skills sector in England responded to an intervention designed to support them in developing the subjectspecialist pedagogy of trainee teachers, a contested issue in the sector for approaching twenty years.…”
Section: Introductionmentioning
confidence: 99%
“…This paper explores how teacher educators think about subject-specialist pedagogy and how they engaged with a particular intervention aimed at extending their knowledge in this area. As with many other aspects of the FE sector, the work of teacher educators is under-researched to the point of invisibility (Crawley, 2018;Springbett, 2018). However, there are broad indications that teacher education is a highly feminised occupation, with often fortuitous entry, and that professional identity, particularly in relation to research activity and ITE as higher education, is relatively weakly developed (Noel, 2006;Author2, 2007;Crawley, 2013).…”
Section: Introductionmentioning
confidence: 99%